Discussion on evaluation and improvement technology of sewage biodegradability - Qiu Qi; Wang Yue; Qiu Li ping (E3S Web of Conferences, 2018)
The lack of water resource and the increasing water pollution have become bottleneck which restricted social progress and economic development. The amount of municipal sewage is large and the pollution is relatively light, so it has a significant potential for recovery and recycle from municipal wastewater. As the most widely used of wastewater denitrification technology in the current water treatment industry, biological denitrification efficiency has been shackled by the lack of inflow carbon source and low C/N ratio. To solve the issue of insufficient carbon source and low nitrogen removal efficiency of traditional biological denitrification technology，the paper summarized the concept, evaluation methodology and significance of biodegradability, several typical techniques for elevating biodegradability also have been mentioned. It will provide reference for process selection in improving the biodegradability of wastewater through analyzing their advantages and disadvantages in the application process.